Determining Consumer Preferences In Choosing Low Budget Accommodation Services In Medan City With Choice-Based Conjoint (CBC) Analysis - Edison Parulian; Yusdiana Yusdiana; Shamir Hasyim Syarif (Manunggal Halim Jaya, 2024)
The hotel accommodation service industry in Medan City has witnessed significant growth following the pandemic, driven by increased business and tourism activities. With over 200 hotels in the city, there is a notable presence of middle-class hotels offering affordable prices. This study aims to determine consumer preferences in choosing low-budget accommodation services using Choice-Based Conjoint (CBC) analysis. The CBC method presents consumers with a series of menus featuring different hotel attributes, such as location, facilities, and price, to identify which attributes most influence their preferences. A sample of 40 respondents was analyzed to identify key factors influencing their hotel choices. The results revealed that consumers prioritize hotels located outside the central city area, with free internet service, basic room amenities, availability of a café or lounge, breakfast services, and non-smoking rooms. The study found that breakfast service is the most important attribute, followed by the availability of non-smoking rooms. These insights can help low budget hotel or managers in Medan City to modify their services to better meet consumer demands and improve market positioning.